Analisis Kedudukan Hukum Lie Detector dalam Pembuktian Tindak Pidana Pembunuhan Berencana - Hatarto Pakpahan; George Renjaan (MLJ Merdeka Law Journal, 2025)
This research aims to analyze the legal standing of using a lie detector in the settlement of the premeditated murder case committed by Jesika Kumala Wongso against I Wayan Mirna Salihin, and to determine the implementation of applying the lie detector in the premeditated murder criminal case. The type of legal research used in this study is normative legal research, and the method of addressing the problem uses the statutory approach and the case approach. The research results show that the legal standing of using the Lie Detector constitutes valid evidence as referred to in Article 184 of the Criminal Procedure Code, namely expert testimony. This is because the results of the examination using the Lie Detector method are then printed out and explained again by an expert who possesses the necessary capability. Therefore, the position of the lie detector in the evidentiary process of the criminal case in Supreme Court Decision Number 498K/PID/2017 is as a complement to the decision-making process, as the judge's conviction was already obtained based on evidence with high probative value, and the Supreme Court judge upheld the decisions of the first-instance and appellate courts.